Dwelling in the Text : Houses in American Fiction. - Chandler, Marilyn R. (UC Press voices revived., 2022)
What is a house? And what can architecture tell us about individual psychology, national character and aspiration? The house holds a central place in American mythology, as Marilyn Chandler demonstrates in a series of ""house tours"" through American novels, beginning with Thoreau's Walden and ending with Toni Morrison's Beloved and Marilynne Robinson's Housekeeping. Chandler illuminates the complex analog.